低硬度圧縮成形体の硬さの評価 - 小林, 信紫; 羽生, 圭吾; 山崎, 敬則 (材料試験技術, 2024)
The hardness of compression molded products cannot be uniformly evaluated because of a wide variety of molded products, but in most cases, the hardness seems to be evaluated either by crushing strength or crushing force. In this study, we focused on compression molded products with low hardness. We will examine both the crushing strength and crushing force for this product and provide knowledge about the appropriate testing method.